1967
DOI: 10.1002/ijc.2910020509
|View full text |Cite
|
Sign up to set email alerts
|

Studies on bladder carcinogens in the human environment I. Naphthylamines produced by pyrolysis of amino acids

Abstract: L-Glutamic acid and L-leucine were pyrolyzed at 500 C and 700 C in a nitrogen atmosphere and the resulting pyrolyzate was analyzed for I -and 2-naphthylamines by column, paper, thin-layer, and gas chromatography. From 100 g of L-glutamic acid pyrolyzed at 700 C, 1.3 mg of 1-naphthylamine and 0.13 mg of 2-naphthylamine were isolated, from 100 g of L-leucine, 0.7 mg and 0.01 mg of the isomers respectively were isolated. When the amino acids were pyrolyzed at 500 C, neither I-nor 2-naphthylamine was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1969
1969
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…2-NA is formed in the pyrolysis of nitrogen-containing organic matter and can occur in nature (60,61). It may occur in the waste streams from plants where it is produced and used; it has been reported to be present in the effluent from certain dyestuff factories in Japan (62).…”
Section: -Naphthylamine (2-na)mentioning
confidence: 99%
See 1 more Smart Citation
“…2-NA is formed in the pyrolysis of nitrogen-containing organic matter and can occur in nature (60,61). It may occur in the waste streams from plants where it is produced and used; it has been reported to be present in the effluent from certain dyestuff factories in Japan (62).…”
Section: -Naphthylamine (2-na)mentioning
confidence: 99%
“…o-Toluidine occurs in the constituents of tobacco smoke (54). Eight U.S. commercial cigarette brands have been found to contain 8.6.-144.3.ng of o-toluidine per cigarette (60). In a study from Turkey (59,64), o-toluidine was found in 34 of the 54 hair dyes tested, at quantities up to 1,547 (µg/g).…”
Section: O-toluidinementioning
confidence: 99%
“…Cigarette smoke contains naphthalene and ammonia (6,10), and one may regard their thermically activated forms as precursors of naphthylamines in the hot zones of a cigarette. -Aminoacids could also be another type of precursors as was demonstrated by pyrolysis studies (11).…”
Section: Resultsmentioning
confidence: 91%
“…2-Naftyloamina powstaje podczas pirolizy związków organicznych zawierających azot [10][11][12]. Już od 1922 r. produkowano ją w celach handlowych, powszechnie wykorzystując przy tym reakcję 2-naftolu z amoniakiem i siarczynem amonu [13].…”
Section: Wstępunclassified